Applying the Transtheoretical Model to evaluate the effect of a call-recall program in enhancing Pap smear practice: a cluster randomized trial - Abdullah, Fauziah; Tin, Tin Su (2013)
Objective: The objective of this study was to evaluate the effect of a callrecall approach in enhancing Pap smear practice by changes of motivation stage among non-compliant women. Methods; A cluster randomized controlled trial with parallel and un-blinded design was conducted between January and November 2010 in 40 public secondary schools in Malaysia among 403 female teachers who never or infrequently attended for a Pap test. A cluster randomization was applied in assigning schools to both groups. An intervention group received an invitation and reminder (call recall program) for a Pap test (20 schools with 201 participants), while the control group received usual care from the existing cervical screening program (20 schools with 202 participants). Multivariate logistic regression was performed to determine the effect of the intervention program on the action stage (Pap smear uptake) at 24 weeks. Results; In both groups, pre-contemplation stage was found as the highest proportion of changes in stages. At 24 weeks, an intervention group showed two times more in the action stage than control group (adjusted odds ratio 2.44, 95 CI 1.29 4.62). Conclusion; The positive effect of a call recall approach in motivating women to change the behavior of screening practice should be appreciated by policy makers and health care providers in developing countries as an intervention to enhance Pap smear uptake.